2008
DOI: 10.1148/radiol.2482071822
|View full text |Cite
|
Sign up to set email alerts
|

Non–Small Cell Lung Cancer Staging: Efficacy Comparison of Integrated PET/CT versus 3.0-T Whole-Body MR Imaging

Abstract: Both PET/CT and 3.0-T whole-body MR imaging appear to provide acceptable accuracy and comparable efficacy for NSCLC staging, but for M-stage determination, each modality has its own advantages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
123
4
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 161 publications
(134 citation statements)
references
References 25 publications
4
123
4
3
Order By: Relevance
“…2,8,10 Abnormal focal FDG uptake accompanied by a corresponding anatomic alteration was considered to be indicative of metastasis. 8 The presence of abnormal uptake was determined qualitatively by comparing the uptake of the lesions in question with that of a mediastinal blood pool in the thorax or that of liver uptake in the abdomen, bones, or the remaining soft tissues. At brain MRI, metastases were considered present when an enhancing nodule(s) or mass was observed in the brain parenchyma on T1W images.…”
Section: Pet-ct and Dedicated Brain Mrimentioning
confidence: 99%
See 1 more Smart Citation
“…2,8,10 Abnormal focal FDG uptake accompanied by a corresponding anatomic alteration was considered to be indicative of metastasis. 8 The presence of abnormal uptake was determined qualitatively by comparing the uptake of the lesions in question with that of a mediastinal blood pool in the thorax or that of liver uptake in the abdomen, bones, or the remaining soft tissues. At brain MRI, metastases were considered present when an enhancing nodule(s) or mass was observed in the brain parenchyma on T1W images.…”
Section: Pet-ct and Dedicated Brain Mrimentioning
confidence: 99%
“…In addition, discrete lesions with abnormally high FDG uptake were regarded as metastatic if they were accompanied by corresponding morphologic alteration on MR images. 8 …”
Section: Coregistered Mri-petmentioning
confidence: 99%
“…On STIR TSE, metastatic nodes have a high signal, while non-metastatic nodes present with a low signal, which influenced Ohno et al [10] to suggest that MRI should be considered as a substitute for PET-CT for the assessment of mediastinal nodes. Yi et al [12] demonstrated that high signal intensity and eccentric cortical thickening or obliterated fatty hilum on T 2 weighted triple-inversion black-blood TSE on MRI can be reliable indicators of malignancy, even in normalsized nodes.…”
Section: Mri Assessment Of N-classificationmentioning
confidence: 99%
“…Liver metastases will show as enhancing nodules on T 1 weighted images. MRI has better contrast than PET-CT in the liver, which facilitates the identification of liver lesions [12]. Similarly, a bone lesion showing enhancement on T 1 weighted images should be considered as suspicious for malignancy [12].…”
Section: Mri Assessment Of M-classificationmentioning
confidence: 99%
See 1 more Smart Citation